2023
DOI: 10.1002/smmd.20230004
|View full text |Cite
|
Sign up to set email alerts
|

Silk‐based conductive materials for smart biointerfaces

Abstract: Silk-based conductive materials are widely used in biointerface applications, such as artificial epidermal sensors, soft and implantable bioelectronics, and tissue/cell scaffolds. Such biointerface materials require coordinated physicochemical, biological, and mechanical properties to meet current practical needs and future sophisticated demands. However, it remains a challenge to formulate silk-based advanced materials with high electrical conductivity, good biocompatibility, mechanical robustness, and in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Currently, the integration of silk into the conductive region of neural electrodes enable cellular activity that enhance neural signal transduction, 44,45 but silk-based conductive neural interface combined with carbon-based material are usually fabricated by eletrospun 46 and chemical synthesis, 47 which may require numerous toxic chemicals solvent and reactants and even lead to the deterioration of beta-crystallization of the silk. Here, our as-developed silk/gelatin/rGO neural interface developed through the electrogelation could produce silk/rGO conductive hydrogel with enhanced crystallization that permits structural stability and electrochemical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the integration of silk into the conductive region of neural electrodes enable cellular activity that enhance neural signal transduction, 44,45 but silk-based conductive neural interface combined with carbon-based material are usually fabricated by eletrospun 46 and chemical synthesis, 47 which may require numerous toxic chemicals solvent and reactants and even lead to the deterioration of beta-crystallization of the silk. Here, our as-developed silk/gelatin/rGO neural interface developed through the electrogelation could produce silk/rGO conductive hydrogel with enhanced crystallization that permits structural stability and electrochemical activity.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, silk has demonstrated multiple advantages, such as biocompatibility, biodegradability, non-toxic degradation products, sterilization, mechanical stability and self-assembly properties [17,18,25]. Moreover, by tuning the chemical composition and the physical structure of silk molecules, various formats of silk-based materials, such as hydrogel, films and 3D porous aerogels, and nanofibers/particles and textiles can be derived from the fibroin solution (organic or aqueous) through different processing techniques [18,25,26]. Some examples of silk-based devices that can be used for drug delivery applications are reported in Figure 1 where some products developed by the authors are shown.…”
Section: Biomaterials For Ddssmentioning
confidence: 99%
“…Among these various forms, due to their versatility, hydrogels stand out as promising biological platforms for cell/drug carriers, extracellular matrix-like (ECM-like) scaffolds and tissue fillers. As injectable solutions, in situ gels, structured matrices, viscous gels and thin sheets, they provide important structural and functional support for cell functions and for sustained release of the desired factors [13,26].…”
Section: Biomaterials For Ddssmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the high adhesion strengths, hydrogel adhesives need to perform some other functions to meet the demands of interface applications 28 . For instance, when using hydrogel adhesive as a wound dressing, it must have good biocompatibility (non‐allergic and non‐toxic) 29,30 . In this scenario, it also needs to have functions such as antibacterial, anti‐oxidation, thermal insulation, and comfortable softness.…”
Section: Introductionmentioning
confidence: 99%